1999
DOI: 10.1172/jci7615
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine SDF-1 stimulates integrin-mediated arrest of CD34+ cells on vascular endothelium under shear flow

Abstract: IntroductionTransplanted human hematopoietic stem cells must retain specific adhesive capacity to interact with the vascular endothelium that lines the bone marrow (BM) (1-3). The mechanisms by which these cells home to and engraft the BM are still obscure. Murine hematopoietic progenitors (HPCs) have been shown to interact in vivo with both P-selectin and E-selectin on vascular endothelium of murine BM (4). In addition, VCAM-1 has been shown to support rolling of HPC on BM endothelium in the absence of endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
428
1
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(456 citation statements)
references
References 77 publications
21
428
1
6
Order By: Relevance
“…A CXCR4-negative progenitor cell line (Kasumi-1) did not display pseudoemperipolesis. The SDF-1/ CXCR4 axis and binding of a4b1 and a5b1 integrins has recently been demonstrated to be involved in the transendothelial migration of haematopoietic progenitor cells (HPC) (Mohle et al, 1998;Jo et al, 2000;Peled et al, 2000), in the rolling and arrest of HPC on vascular endothelial cells under shear flow (Peled et al, 1999b), and in human HPC mobilization and homing (Prosper et al, 1998;Peled et al, 1999a;Kollet et al, 2001). It has also been demonstrated that HSC are uniquely selective in their chemotactic responsiveness to SDF-1, suggesting that this chemokine is the key factor for homing of HSC to the marrow that cooperates with integrins, in particular a4b1 integrins (Wright et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CXCR4-negative progenitor cell line (Kasumi-1) did not display pseudoemperipolesis. The SDF-1/ CXCR4 axis and binding of a4b1 and a5b1 integrins has recently been demonstrated to be involved in the transendothelial migration of haematopoietic progenitor cells (HPC) (Mohle et al, 1998;Jo et al, 2000;Peled et al, 2000), in the rolling and arrest of HPC on vascular endothelial cells under shear flow (Peled et al, 1999b), and in human HPC mobilization and homing (Prosper et al, 1998;Peled et al, 1999a;Kollet et al, 2001). It has also been demonstrated that HSC are uniquely selective in their chemotactic responsiveness to SDF-1, suggesting that this chemokine is the key factor for homing of HSC to the marrow that cooperates with integrins, in particular a4b1 integrins (Wright et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that HSC are uniquely selective in their chemotactic responsiveness to SDF-1, suggesting that this chemokine is the key factor for homing of HSC to the marrow that cooperates with integrins, in particular a4b1 integrins (Wright et al, 2002). Peled et al (1999b) suggested that SDF-1 expression on vascular endothelium initiates HSC homing to the marrow, as demonstrated by shear flow adhesion assays and anti-SDF-1 staining of marrow microvessels. Our study extends this concept by demonstrating that stromal cells are active players in HSC migration.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that primitive bone marrow cells migrate to the bone in an integrin mediated SDF-1/protein kinase C signaling dependent mechanism [62]. Engraftment studies on NOD/SCID also shows that SDF1/CXCR4 activates several integrins such as VLA-4, VLA-5; and to a lesser degree, LFA-1 on CD34+ progenitor cells which enhances the process of engraftment [63,64]. Incorporation and colocalization of CXCR4 and Rac-1 into lipid rafts could enhance the chemotaxis of hematopoietic stem progenitor cells (HSPC) towards the bone [65].…”
Section: Chemotaxis Towards Bonementioning
confidence: 96%
“…Stromal-derived factor 1 (SDF-1a, also called CXCL12) belongs to the a-chemokine family and is constitutively expressed by bone marrow (BM) endothelial cells. 26,27 SDF-1 exerts most of its biological effects by binding to the G-protein-coupled CXCR4 receptor, which is expressed on many cell types including some CD34 þ CD38 À cells. 28,29 SDF-1 and CXCR4 are central to hematopoiesis, chemotaxis, and engraftment of hematopoietic stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 99%